Stir bar sorptive extraction for the analysis of beverages and foodstuffs - Tredoux, A. G. J. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2008.